Information Fusion and Geographic Information Systems Proceedings of the Fourth International Workshop, 17-20 May 2009 - Popovich, Vasily V.; Claramunt, Christophe.; Schrenk, Manfred.; Korolenko, Kyrill V. (Lecture Notes in Geoinformation and Cartography,, 2009)
The Workshop Proceedings introduce research results received in the areas of GIS and technologies in relation with Corporate Information Systems (CIS). In this context the attention is also paid to a wide range of problems of data harmonization, integration and fusion (HIF) concept regarding CIS. The book deals with conventional problems of information integration, development of GIS and GIS-applications to a wide spectrum of information systems considerably varying in purpose and scale. New class of GIS intelligent GIS is considered including principles of their developing and programming technologies. Special attention is drawn to ontologies development and their use in GIS and GIS-applications.